Elderly depressive disturb: the social context and environment as generators of such disturbs - Carla Targino da Silva Bruno; Marília Braga Marques; Maria Josefina da Silva (Rev Rene)
Living in institutions for the elder may be a result of the low quality of life or family relations. Also, for the lack of their own resources, high dependence, lack of references caused by the death of people who were meaningful for them. However, living at home may prevent the elder from being in the same situation of the institutionalized when we refer to social and family context. The aim of this study was to evaluate the percentage of elderly people that suggest depressive disturbs and the relation between the elder life time and the presence of depression indicators. Correlational descriptive studies were accomplished in 3 institutions as well as in two groups of elderly people who had close companionship. The Depression Geriatric Scale was applied and the results demonstrated that in meaningful aspects of elderly life, the ones who are participants in group activities have more indications of geriatric depression than the institutionalized ones. We conclude that the actions led to the elder must include this extremely meaningful fact to the life quality of the elder ant to his/her staying in the family environment.